A docência na Fisioterapia: uma necessária formação pedagógica - Oliveira, Ana Larissa Costa de (2014)
Introduction: The course of physiotherapy as upper level was introduced in Brazil by Decree Law No. 938/69 on 13 October 1969 in Article 5 of this Decree, II , found the legal framework that allows the Physiotherapist exercise teaching in teaching intermediate or higher level institutions. After this decree, other questions about the training of teaching undergraduate physiotherapy, where physical therapists, mostly, still being formed by curricula whose activity is restricted to the technical capacity to rehabilitate, encouraging technicist training appeared not possessing the pedagogical training for teaching. Objective: Discuss the process of pedagogical training of physiotherapists teachers in higher education. Methodology: This was a qualitative study using semi-structured interviews accompanied by descriptive analysis of the data obtained through identification cards to characterize the subjects, who were physiotherapists teachers of a private IES. After this phase, interviews were analyzed by content analysis framework of Bardin (2011). Results: The study was divided into three units of records (UR). The UR1: motivation of the choice of teaching activity with categories of skills and labor market; the UR2: playing with attitudes related to teacher-student relationship and teaching practices and UR3: categories: route of teaching practice with the types of challenges and opportunities found in the career of teaching. Final Thoughts: In discussing the need for teacher training, It can be seen by the majority of teachers that are not educationally prepared to exercise this function, however, it is observed that most continually search for training, courses, training improvements and stricto sensu to update and better qualifications for teaching and has been suggested as a way of improving teaching practice one training in person at the IES itself. We further note that the analysis of this issue led to the development of new research including the perception of students on teaching in physical therapy.